Conservation of Major L1 and Variability of Minor L2 Capsid Late Protein Genes in Human Papillomavirus of Indonesia Variants - Nuswantara, Sukma; Prana, Titik K; Wulandari, Dwi; Widyowati, Henni; Anzela, Vera; Levy, Dea; Cahyadi, Petrus; Tjandra, Lukas D (ANNALES BOGORIENSES, 2010)
Human Papilloma VirusÂ  (HPV) has an out standing feature for its vast intraspecies variability. Of all known 100 types orÂ  more, 15 t ypes of them are classified as high riskÂ  because of their occurrenceÂ  inÂ  more than 95% of cervical cancer cases. Among all genes in their genome, E6 and E7 genes are considered oncogenes and have close relevance with their pathogenicity, whilst L1 and L2 ge nes produce capsid proteins that directly interact with theirÂ  hostÂ  receptors.Â  ConsideringÂ  theÂ  importanceÂ  ofÂ  L1Â  andÂ  L2Â  inÂ  host-receptorÂ  relationship,Â  weÂ  triedÂ  to investigate their molecular variability thereby uncover their specificity as Indonesian variant s. Here we reported about the conservation of L1 minor capsid protein and variability of L2 capsid protein among high-risk types Human Papilloma Virus (HPV). The results indicated that L1 DNA was relatively more conserved than its L2 counterpart Also it was indicated that the middle part of either L1 or L2 CDSâ showed more DNA variability than thoseÂ  atÂ  theirÂ  upstreamÂ  sequences.Â  ItÂ  isÂ  concludedÂ  thatÂ  L2Â  middleÂ  sequencesÂ  areÂ  importantÂ  factorsÂ  for intraspecific variations found in HPV of Indonesian variants. Â  Keywords: Human Papilloma Virus (HPV), L1 gene, L2 gene, cervical cancer, high risk HPV